Acute Transverse Myelitis Associated with Buserelin Use during IVF. (28th March 2013) - Alleemudder, Djavid I.; Sadek, Khaled; Fountain, Shaun; Davies, Sallie
Abstract : A healthy woman undergoing in vitro fertilization (IVF) developed acute transverse myelitis (ATM) following the use of Buserelin. ATM has a multifactorial etiology and may develop as a result of the activation of immune responses. Infectious agents have been postulated as possible triggers of an immune response (Sá, 2009). Gonadotropin-releasing agonists may have a similar role and trigger the acceleration of preexisting disease by the activation of immune responses (Ho et al., 1995, and Umesaki et al., 1999).